“My dearest dreams are of the Netherlands”: Pál Pántzél’s manuscript autobiography and his university years in Leiden from 1782 to 17851 - Fazakas, Gergely Tamás (Acta Neerlandica, 2015)
Pál Pántzél (1755-1831) was a Hungarian Calvinist pastor and scholar in Transylvania. Following his years in the Reformed College of Kolozsvár (Cluj, present-day Romania), Pántzél was a student of the Staten College at the University of Leiden between 1782 and 1785. He kept a manuscript autobiography, and wrote down his life story in Hungarian. This autobiography is interesting from various perspectives, including regional history, the social and church history of Transylvania, the history of education and so forth. Pántzél wrote extensively about his Leiden university years, which he considers the most beautiful memories of his life, but also includes details of the conditions in which he travelled, as well as the organisation of the trip and the details of the outward journey. In the present study I primarily interpret Pántzél’s notes on his years at the University of Leiden, in the context of early modern travel literature and the history of studying in the Netherlands.